THE EFFECT OF BRASS (Cu-Zn) CATALYTIC CONVERTER ENGINE PERFORMANCE - Ellyanie Ellyanie; Devan Oktabri H (Indonesian Journal of Engineering and Science (IJES), 2021)
Installing a catalytic converter in the exhaust is a typical method of reducing engine exhaust emissions. Catalytic converters have been shown to lower exhaust pollutants while enhancing engine performance. The influence of the number of brass catalyst plates (Cu-Zn) on the Performance of the commercial Yamaha Jupiter MX motorcycle engine manufactured in 2007 was investigated in this study. The catalyst is installed in the motorbike exhaust, with the number of catalyst plates varying between 5 and 8, and a conventional uncatalyzed exhaust serving as a comparison. Torque, power, specific fuel consumption, and thermal efficiency are among the performance factors that will be considered. A prony brake dynamometer was used to conduct torque and power measurements. The results indicate that exhaust with eight catalyst plates can improve engine performance more than an exhaust with five catalyst plates. Furthermore, exhausts equipped with eight catalyst plates can boost engine efficiency by an average of 17.65%. Thus, increasing the number of catalyst brass plates improves the machine's efficiency.